Applicability of UASB sludge to agricultural lands - (:unkn) unknown (IWA PUBLISHING, 1998)
Investigation of dewaterability and applicability of UASB sludge to agricultural lands were the objectives of this study. Under laboratory conditions, 90% of sludge moisture percolated in 4 days. Desorption of metals such as copper and lead did not occur under normal conditions. Desorption of metals occurred only at pH I or less. UASB sludges have strong affinity for metals. The nutrient value of these sludges are small compared to commercial fertilizers. (C) 1998 IAWQ. Published by Elsevier Science Ltd.
Keywords: adsorption; desorption; dewaterability; land treatment; nutrient; UASB sludge